Agreement between accelerometer-assessed and self-reported physical activity and sedentary time in colon cancer survivors - Boyle, Terry; Lynch, B.; Courneya, K.; Vallance, J. (Springer, 2014)
Purpose: Research conducted on the general population indicates self-reported measures of physical activity and sedentary behaviour are inaccurate when compared with objective measures; however, it is not clear if this also applies to cancer survivors. In this study, we compared accelerometer-based and self-reported measures of moderate- to vigorous-intensity physical activity (MVPA) and sedentary time among colon cancer survivors. Methods: A total of 176 colon cancer survivors, recruited from the Western Australia and Alberta cancer registries, wore an Actigraph GT3X+ accelerometer for 7 days and completed self-reported questions about recent MVPA (Godin Leisure-Time Exercise Questionnaire) and usual sedentary time (Marshall Domain-Specific Sitting Questionnaire). Accelerometer data were processed using 60-s epochs and summarized using Freedson’s cut points. Spearman’s rho and intraclass correlation coefficients (ICCs) were used to assess correlation and agreement for daily MVPA and sedentary time estimates from the two methods. Results: Total mean minutes per day spent in MVPA was 12 min based on accelerometer data and 26 min based on self-reported data (P Difference  < 0.01). Correlation between the methods was fair (rho = 0.51); however, agreement was poor (ICC = 0.33). Mean daily time spent sedentary was similar in both methods (∼8.5 h); however, both correlation and agreement were poor (rho = 0.19, ICC = 0.16). Conclusions: We found fair correlation but poor agreement between the self-reported and accelerometer-based assessments of MVPA used in this study. For sedentary time, both correlation and agreement between the two methods were poor. Studies of colon cancer survivors using these self-report measures are likely to have a considerable amount of exposure misclassification.